Characteristics of Duplex Angular Contact Ball Bearing with Combined External Loads and Angular Misalignment - Tengfei Xu; Lihua Yang; Kai Wang (Applied Sciences, 2020)
As a kind of common phenomenon in practical engineering, misalignment error considerably changes the working performance of bearing. However, it has rarely attracted attention in the study of duplex angular contact ball bearings (DACBBs). To evaluate the influence of misalignment on DACBB, an analytical model of DACBB considering combined loads and angular misalignment is established for back-to-back, face-to-face, and tandem configurations. According to the geometrical relationship inside the bearing, the deformations caused by external load and angular misalignment are systematically analyzed. On this basis, the effects of external load, axial preload, and angular misalignment on the displacement, maximum contact load, contact load distribution, contact angle, and fatigue life of DACBB are analyzed. The results demonstrate the high dependence of the contact load and contact angle on the above factors. Angular misalignment causes the fluctuation of contact load and contact angle distributions along the azimuth angle of a rolling ball. Nonlinear relationships between fatigue life of DACBB, angular misalignment, and axial preload are obtained. The occurrence of angular misalignment considerably decreases the fatigue life of DACBB. The results suggest the necessity of angular misalignment analysis for DACBB.